ANALISIS JARINGAN EKSTERNAL ICMI ORDA ACEH BARAT - Eka Marisa; Mursyidin Zakaria; Reni Juliani (Universitas Teuku Umar, 2019)
The purpose of this study was to find out about how the role of ICMI (Indonesian Muslim Intellectuals Association) in building external communication networks. The data collection method used for this research is qualitative. Data collection techniques used were direct observation and interview. This research is located in West Aceh Regency, precisely in JLN Sisingamangaraja No. 99 Gampa Village, Meungaboh Dirundeng STAIN Campus and informants in this study amounted to 8 people. Data analysis was performed using a qualitative descriptive approach. The results of the study conducted by the author show that the external communication network conducted by the ICMI organization (Indonesian Muslim Cendiawan Association) uses 3 indicators in it, namely (1) personal networks, where the relationships owned by the chairman and the management tend to be more frequent. (2) organizational networks, a link of elements in which they are interconnected. Building cooperation with other organizations, while the network is built usually through a daily board. (3) Global Network, an object that connects the ICMI network with other institutions. From the results the authors consider that the network built by ICMI of the West Aceh Order tends to be carried out by the daily chairman, the lack of involvement of the management in building the external network at the institution due to the factor of the vacuum of activities that had been agreed upon previously and the busyness of the management who work as lecturers, entrepreneurs, dayah leaders and so on. However ICMI the West Aceh Orda also conducts good activities at the national level.